2005
DOI: 10.1007/s10995-005-2452-6
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering of Risk Behaviors Among Caribbean Youth

Abstract: Health compromising behaviors cluster among Caribbean youth with associations being stronger for females. Initiating sexual activity was a predictor of other risk behaviors with the likelihood increasing among older adolescents and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 29 publications
6
80
0
5
Order By: Relevance
“…Similarly, older youth reported higher levels of engagement and witness to youth violence. These findings are consistent with the previous studies' findings in the Caribbean (Blum et al, 2003;Katz, 2015;Katz & Fox, 2010;Ohene et al, 2005). Regarding risk and protective factors, no differences were found in protective factors between females and males.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, older youth reported higher levels of engagement and witness to youth violence. These findings are consistent with the previous studies' findings in the Caribbean (Blum et al, 2003;Katz, 2015;Katz & Fox, 2010;Ohene et al, 2005). Regarding risk and protective factors, no differences were found in protective factors between females and males.…”
Section: Resultssupporting
confidence: 93%
“…Crime or violence in CARICOM Member States is characterized by homicides and wounding and is associated with the illicit drug trade, gang warfare, revenge and perception of disrespect. Young men are disproportionally affected when compared with girls and younger boys (Blum et al, 2003;Katz, 2015;Katz & Fox, 2010;Ohene et al, 2005). According to the UNDP (2012), approximately six percent of youth may have been affiliated with a gang.…”
Section: Literature Review Youth Violence In the Caribbean Community mentioning
confidence: 99%
“…In section IV, we present the results, and we end with a discussion of the findings in section V. Wu, McMahon and Dodge, 2010). For example, in the Caribbean, Ohene et al (2005) find that initiation of sexual activity is positively associated with gang involvement and weapon-carrying in young adolescents and even more risk behaviors in older adolescents.…”
Section: Sex Violence and Drugs Among Latin American And Caribbean mentioning
confidence: 90%
“…We chose control variables on the basis of previous studies with data from the Caribbean that have been identified as being associated with the outcome behaviors of interest. Being male has been found to be an important predictor of the likelihood of adolescents to engage in violent behavior, substance abuse, and early sexual activity (Meeks Gardner, 2003;Blum and Ireland, 2004;Kurtz, Douglas and Lugo, 2005;Ohene et al, 2005;Maharaj, Nunes and Renwick, 2009). …”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation